THE IMPORTANCE OF WORKS OF VISUAL ART IN THE AESTHETIC PERCEPTION OF THE WORLD (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Annotation: in this article, opinions are expressed about aesthetic perception, its content, the role of visual art works in aesthetic perception of the world, and the importance of developing aesthetic perception in students through visual art.